Performance in the Borderlands
XI, 283 p.
Keywords: A border is a force of containment that inspires dreams of being overcome and crossed; motivates bodies to climb over; and threatens physical harm. This book critically examines a range of cultural performances produced in relation to the tensions and movements of/about the borders dividing North America, including the Caribbean.